Skeptisisme Epistemologis: Mempertanyakan Kebenaran Yang Absolut - Ekhat Binti Patangun; Mozes lawalata (Jurnal Pendidikan Agama dan Teologi, 2024)
Rational thinkers need the ability to think critically but it is not enough just to do that, it must be with real and visible evidence. In this discussion the author uses a quantitative method with a descriptive approach which makes it possible to answer questions that require absolute answers, namely by presenting the evidence that exists because absolute truth cannot be seen through mystical/prological thinking.